2018
DOI: 10.1053/j.gastro.2018.05.033
|View full text |Cite
|
Sign up to set email alerts
|

GABAA Receptor Subtypes Regulate Stress-Induced Colon Inflammation in Mice

Abstract: We found stress to increase expression of Gabra3 and induce inflammation in mouse colon, together with impaired barrier function. The in vitro pharmacologic activation of α3-GABARs recapitulated colonic inflammation, whereas α1/4/5-GABAR ligands were anti-inflammatory. These proteins might serve as therapeutic targets for treatment of colon inflammation or inflammatory bowel diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…; Seifi et al . ), it is important to note that GABA receptor activation in the colon may also be associated with deleterious side‐effects. Consistent with this suggestion, a recent study shows that activation of GABA A receptors in colon epithelium exacerbates acute colitis (Ma et al .…”
Section: Discussionmentioning
confidence: 99%
“…; Seifi et al . ), it is important to note that GABA receptor activation in the colon may also be associated with deleterious side‐effects. Consistent with this suggestion, a recent study shows that activation of GABA A receptors in colon epithelium exacerbates acute colitis (Ma et al .…”
Section: Discussionmentioning
confidence: 99%
“…encode for genes involved in GABA production, suggesting a microbial participation in the production of this neurotransmitter within the gut [67,68]. Indeed, GABA-A receptors have been recently identified in the mouse colon [69,70]. Interestingly, we recently observed that rat colon expresses steroidogenic capability and, in particular, an high production of a T metabolite, such as the 3α-diol [71].…”
Section: Discussionmentioning
confidence: 96%
“…qPCR amplifications were performed to assess changes in the mRNA levels for the following inflammatory genes, using pre-designed Taqman primers/probes purchased from Life Technologies (ThermoFisher scientific): IL1β (Mm00434228_m1); TNF-α (Mm00443258_m1); IL 6 (Mm00446190_m1); CSF1 (Mm00432686_m1); CCL2 (Mm00441242_m1) and CCL3 (Mm00441259_g1), in samples from the LC and hippocampus, according to our previously published protocols (Seifi et al 2018). Gapdh (assay ID: Mm99999915_g1) gene expression was used as the housekeeping gene.…”
Section: Methodsmentioning
confidence: 99%